Antioxidant Activity of Melissa Officinalis Leaves - Koksal, E.; Bursal, Ercan; Dikici E.; Tozoglu F.; Gulcin I. (My University, 2011)
The purpose of this study was to evaluate antioxidant activities of water extract of Melissa officinalis (WEM) and ethanol extract of M. officinalis (EEM), comparatively. The WEM and EEM were evaluated for their radical scavenging activities by means of the DPPH and DMPD assays. WEM scavenged radicals effectively with IC 50 values of 31.4 ?g/mL for DPPH free radical and 60.5 ?g /mL for DMPD cation radical. Similarly, EEM scavenged radicals effectively with IC 50 values of 202.7 ?g/mL for DPPH free radical and 120.9 ?g/mL for DMPD cation radical. Also, total reducing power of WEM was found higher than EEM with both potassium ferricyanide reduction (FRAP) and cupric ions reduction capacity methods (CUPRAC). The present study showed that WEM have effective antioxidant and radical scavenging activities as compared to EEM. © 2011 Academic Journals.
Keywords: Antioxidant activity; Melissa officinalis; Radical scavenging; Reducing power